Method for representing zanthoxylum of SiO2-based Janus material

Through infrared testing and fluorescein labeling methods, the simplicity problem of SiO2-based Janus material was solved, effective characterization of the two-sided properties of the material was realized, and the asymmetry of SiO2-based Janus material was demonstrated.

CN119125054APending Publication Date: 2024-12-13BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411177664.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art lacks a simple and effective method to verify the bilaterality of Janus materials, especially the characterization method of SiO2-based Janus materials is not perfect enough.

Method used

Infrared tests were used to combine isothiocyanate fluorescein, and mixed with fluorescein by crushing SiO2-based Janus material, and observed the fluorescence phenomenon using laser scanning confocal microscope to distinguish the distribution of amino groups on the inner surface and epoxy functional groups on the outer surface.

Benefits of technology

The effective characterization of the bilaterality of SiO2-based Janus material is achieved, which is simple and easy to operate, and can clearly distinguish the inner surface of the amino group and the outer surface distribution of the epoxy group, and infer the asymmetry of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119125054A_ABST
    Figure CN119125054A_ABST
Patent Text Reader

Abstract

The invention discloses a method for characterizing two sides of a SiO2-based Janus material, the SiO2-based Janus material comprises SiO2-based hollow microspheres, the inner surfaces of the SiO2-based hollow microspheres have amino groups, the outer surfaces of the SiO2-based hollow microspheres have epoxy functional groups, the SiO2-based Janus material is crushed and then mixed with fluorescein isothiocyanate, and the SiO2-based Janus material is subjected to an infrared test. By adopting the method, the zanthoxylum of the SiO2-based Janus material can be effectively represented, and the method has the characteristics of simplicity, easiness in operation and good effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of material characterization, and in particular, relates to a method for characterizing the two-sidedness of SiO2-based Janus materials. Background Art

[0002] Janus materials are a new type of functional materials with spatial partitioning characteristics of composition or properties. Due to its surface structure with two different chemical compositions, it has attracted much attention in the field of materials research. Janus materials provide a new way to solve the functional integration and coupling of composite materials, and have important application prospects in assembling superstructures, interface regulation and functionalization, green chemical industry and environmental protection, high performance of polymers and high-value recycling. At present, it has been widely used in hydrophobic films, directional magnetic control transmission, biomedicine, oil displacement technology and other fields.

[0003] Amphiphilic Janus nanosheets refer to asymmetric sheet-like nanomaterials with one side being hydrophilic and the other side being hydrophobic. They usually have high interfacial activity. This asymmetry of surface properties makes Janus materials have good amphiphilicity and are considered to be a solid surfactant. They not only have the hydrophilic and lipophilic properties of surfactant molecules, but also have unique properties such as the quantum effect of nanomaterials. However, there are currently few methods for verifying Janus structures, and further exploration of more concise and effective methods is needed. Summary of the invention

[0004] The invention provides a method for characterizing a SiO2-based Janus material. The method can effectively characterize the two-sidedness of the SiO2-based Janus material, and the method has the characteristics of being simple, easy to operate and having a good effect.

[0005] The first aspect of the present invention provides a method for characterizing the two-sidedness of a SiO2-based Janus material. The SiO2-based Janus material comprises SiO2-based hollow microspheres, the inner surface of the SiO2-based hollow microspheres has amino groups, and the outer surface of the SiO2-based microspheres has epoxy functional groups. The SiO2-based Janus material is crushed and mixed with isothiocyanate fluorescein, and the SiO2-based Janus material is subjected to infrared testing.

[0006] Furthermore, the preparation method of the SiO2-based Janus material includes: mixing a silicon source with silane coupling agents KH550, KH560, an oil-in-water type surfactant and an organic solvent to obtain a mixed oil phase; mixing the mixed oil phase with an aqueous solution containing a pH regulator while stirring to obtain a mixed emulsion; heating the mixed emulsion to react; and freeze-drying the product obtained by the heating reaction to obtain the SiO2-based Janus material.

[0007] Furthermore, the silicon source includes at least one of TEOS, tetramethyl silicate and propyl orthosilicate.

[0008] Furthermore, the water-in-oil surfactant includes at least one of Span80, Span85 and Span60.

[0009] Furthermore, the organic solvent includes at least one of xylene oil, toluene and liquid paraffin.

[0010] Furthermore, the mass ratio of the silicon source to the silane coupling agent KH550, the KH560, the water-in-oil surfactant and the organic solvent is (100): (15-20): (20-40): (100-130): (1000-1500).

[0011] Furthermore, the pH of the aqueous solution containing the pH adjuster is 2-5.

[0012] Furthermore, the mass ratio of the mixed oil phase to the aqueous solution containing the pH regulator is (100-150):(15-20).

[0013] Furthermore, the heating temperature is 70-80°C and the heating time is 10-12h.

[0014] Furthermore, the SiO2-based Janus material has a particle size of 10 μm-80 μm and a wall thickness of 0.5 μm-1.5 μm.

[0015] Compared with the prior art, the present invention has at least the following beneficial effects:

[0016] The method of the present invention combines infrared and isothiocyanate fluorescein to characterize SiO2-based Janus materials. -1 The characteristic peak of NH is at 1050cm -1The characteristic peak of -COC is at , indicating that the obtained Janus material has the amino group of KH550 and the epoxy group brought by KH560, and the SiO2-based Janus material is crushed and mixed with fluorescein isothiocyanate (FITC, FITC is a fluorescent dye with the function of specifically labeling amino functional groups), and then the FITC-stained polymerization product is characterized by fluorescence using an Olympus FV1000 laser scanning confocal microscope, and FITC is excited under 495nm laser irradiation to produce bright green fluorescence, and its fluorescence image is captured by a laser scanning confocal microscope, and complete spherical and agglomerated broken flaky structures appear in the field of view at the same time, and after FITC staining and laser excitation, clear green fluorescence is observed only on the broken flaky structures, while there is no green fluorescence in the complete hollow spheres. This is because after the Janus hollow sphere is broken, the inner surface with amino groups is exposed to the outside on the fragments, and FITC combines with the amino groups on the inner surface. Bright fluorescence can be observed after excitation; since the FITC dye cannot enter the interior of the complete Janus sphere, the amino groups on the inner surface are not labeled by FITC, and the epoxy groups on the outer surface do not react with FITC. No fluorescence is observed after laser excitation, indicating that the amino groups are formed on the inner surface of the SiO2-based Janus material, and it is inferred that the epoxy functional groups are formed on the outer surface of the SiO2-based Janus material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0018] Figure 1 Reaction model diagram for preparing SiO2-based Janus materials;

[0019] Figure 2 This is a photo of SiO2-based Janus hollow spheres of Example 1;

[0020] Figure 3 The infrared spectra of SiO2-based Janus hollow spheres and SiO2 obtained in Example 1;

[0021] Figure 4 This is a SEM image of the SiO2-based Janus hollow sphere obtained in Example 1;

[0022] Figure 5 The fluorescence image of the SiO2-based Janus hollow sphere obtained in Example 1 after being stained was taken by a laser scanning confocal microscope;

[0023] Figure 6 This is a SEM image of the SiO2-based Janus hollow sphere obtained in Example 2;

[0024] Figure 7 This is a SEM image of the SiO2-based Janus hollow sphere obtained in Example 3;

[0025] Figure 8 This is the SEM image of the SiO2-based Janus hollow spheres obtained in Example 4. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments, and the following examples are only descriptive, not restrictive, and cannot be used to limit the scope of protection of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0027] The first aspect of the present invention provides a method for characterizing the two-sidedness of a SiO2-based Janus material. According to an embodiment of the present invention, the SiO2-based Janus material comprises SiO2-based hollow microspheres, the inner surface of the SiO2-based hollow microspheres has amino groups, the outer surface of the SiO2-based microspheres has epoxy functional groups, the SiO2-based Janus material is crushed and mixed with isothiocyanate fluorescein, and the SiO2-based Janus material is subjected to infrared testing.

[0028] Therefore, the present invention combines infrared and isothiocyanate fluorescein to characterize SiO2-based Janus materials. -1 The characteristic peak of NH is at 1050cm -1The characteristic peak of -COC is at , indicating that the obtained Janus material has the amino group of KH550 and the epoxy group brought by KH560, and the SiO2-based Janus material is crushed and mixed with fluorescein isothiocyanate (FITC, FITC is a fluorescent dye with the function of specifically labeling amino functional groups), and then the FITC-stained polymerization product is characterized by fluorescence using an Olympus FV1000 laser scanning confocal microscope, and FITC is excited under 495nm laser irradiation to produce bright green fluorescence, and its fluorescence image is captured by a laser scanning confocal microscope, and complete spherical and agglomerated broken flaky structures appear in the field of view at the same time, and after FITC staining and laser excitation, clear green fluorescence is observed only on the broken flaky structures, while there is no green fluorescence in the complete hollow spheres. This is because after the Janus hollow sphere is broken, the inner surface with amino groups is exposed to the outside on the fragments, and FITC combines with the amino groups on the inner surface. Bright fluorescence can be observed after excitation; since the FITC dye cannot enter the interior of the complete Janus sphere, the amino groups on the inner surface are not labeled by FITC, and the epoxy groups on the outer surface do not react with FITC. No fluorescence is observed after laser excitation, indicating that the amino groups are formed on the inner surface of the SiO2-based Janus material, and it is inferred that the epoxy functional groups are formed on the outer surface of the SiO2-based Janus material.

[0029] According to a specific embodiment of the present invention, the method for preparing the SiO2-based Janus material comprises:

[0030] S1: Mix the silicon source with silane coupling agents KH550, KH560, water-in-oil surfactant and organic solvent to obtain a mixed oil phase.

[0031] In this step, the silicon source includes at least one of TEOS, tetramethyl silicate, and propyl orthosilicate; further, the water-in-oil surfactant includes at least one of Span80, Span85, and Span60; further, the organic solvent includes at least one of xylene oil, toluene, and liquid paraffin; the mass ratio of the silicon source to the silane coupling agent KH550, the KH560, the water-in-oil surfactant, and the organic solvent is 100:(15-20):(20-40):(100-130):(1000-1500).

[0032] S2: Mixing the mixed oil phase with an aqueous solution containing a pH adjuster while stirring to obtain a mixed emulsion

[0033] In this step, the aqueous solution is added dropwise to the mixed oil phase with stirring (stirring speed is 6000-10000rpm), and high-speed shearing is performed for 5-10 minutes to obtain a mixed emulsion. Furthermore, the aqueous solution containing the pH regulator is an aqueous solution containing hydrochloric acid; the pH of the aqueous solution containing the pH regulator is 2-5; the mass ratio of the mixed oil phase to the pH regulator is (100-150): (15-20). Thus, by controlling the proportion of each material, a SiO2-based Janus material with controllable particle size and wall thickness can be obtained. Specifically, the particle size of the SiO2-based Janus material of the present application is 10μm-80μm, and the wall thickness is 0.5μm-1.5μm.

[0034] S3: heating the mixed emulsion for reaction

[0035] In this step, the mixed emulsion is heated in an oil bath for reaction, and the water-in-oil emulsion droplets containing silane coupling agents KH550, KH560, silicon source, and are hydrolyzed and cross-linked in an acidic environment to form a whole, and the inner surface of the formed SiO2-based Janus hollow sphere is formed by cross-linking KH550 and TEOS, so that the inner surface carries amino groups, and the outer surface is formed by cross-linking KH560 and TEOS, carrying epoxy functional groups. The reaction model is as follows: Figure 1 shown.

[0036] Furthermore, the heating temperature is 70-80°C and the heating time is 10-12h.

[0037] S4: freeze-drying the product obtained by the heating reaction to obtain the SiO2-based Janus material.

[0038] In this step, the solid product obtained by the above heating reaction is filtered and washed multiple times with ethanol as the solvent to remove the unreacted KH550, KH560, oil-in-water type surfactants, organic small molecules such as organic solvents and aqueous solutions, and then placed in a vacuum freeze dryer and vacuum freeze-dried at -60°C for 6 hours to remove the ethanol solvent to obtain a SiO2-based Janus material.

[0039] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments. The present invention may also have other various embodiments, and those skilled in the art may make various corresponding changes and deformations according to the present invention without departing from the spirit and essence of the present invention, but these corresponding changes and deformations shall all belong to the protection scope of the claims attached to the present invention.

[0040] Example 1

[0041] 5.21g of TEOS, 0.92g of KH550, 1.20g of KH560, and 6.01g of water-in-oil surfactant Span80 were added to 70g of xylene oil, and 10g of deionized water (containing hydrochloric acid solution) with a pH of 2.5 was added dropwise, and then sheared at a high speed of 10000rpm for 10min to form a uniform emulsion, which was then poured into a flask and stirred in an oil bath at 70°C for 10h to obtain a SiO2 solid product, which was filtered and washed several times with ethanol as a solvent to remove the small organic molecules dissolved in xylene, and then placed in a vacuum freeze dryer, frozen at -60°C for 3h and vacuum dried for 3h to obtain SiO2-based Janus hollow spheres. The photo of SiO2-based Janus hollow spheres is shown in the figure. Figure 2 As shown, the FTIR spectrum is Figure 3 As shown, compared with pure SiO2, 2926cm -1 and 2852cm -1 The peaks of asymmetric stretching vibration and symmetric stretching vibration of -CH2 indicate that the silane coupling agent with -CH2 undergoes a cross-linking reaction with TEOS and combines together; 1461cm -1 The NH bending vibration peak is at 1050cm -1 The stretching vibration peak of -COC is at , indicating that the obtained Janus material has amino groups of KH550 and epoxy groups brought by KH560. Figure 4 As shown, the diameter of the SiO2-based Janus hollow spheres is about 10 μm, and the shell wall thickness is about 1.2 μm. The obtained hollow spheres are dispersed in ethanol and mechanically crushed by an ultrasonic cell crusher for 10 minutes to obtain the desired SiO2-based Janus nanosheets, using 3.0s / 3.0s intermittent ultrasound and a crushing power of 390w. The SiO2-based Janus material is then crushed and mixed with fluorescein isothiocyanate (FITC, FITC is a fluorescent dye with a specific labeling function for amino functional groups), and then the FITC-stained polymer product is characterized by fluorescence using an Olympus FV1000 laser scanning confocal microscope. FITC is excited under 495nm laser irradiation to produce bright green fluorescence, and its fluorescence image is captured by a laser scanning confocal microscope, as shown in FIG. Figure 5As shown in the figure, both complete spheres and agglomerated fragmented flake structures appear in the field of view. After FITC staining and laser excitation, clear green fluorescence is observed only on the fragmented flake structures, while there is no green fluorescence in the complete hollow sphere. This is because the inner surface with amino groups on the fragments of the broken Janus hollow sphere is exposed to the outside, and FITC combines with the amino groups on the inner surface, and bright fluorescence can be observed after excitation; the amino groups on the inner surface of the complete Janus sphere are not labeled by FITC because the FITC dye cannot enter the interior of the hollow sphere, and the epoxy groups on the outer surface do not react with FITC. No fluorescence is observed after laser excitation, indicating that the amino groups are formed on the inner surface of the SiO2-based Janus material, and the epoxy functional groups are formed on the outer surface of the SiO2-based Janus material.

[0042] Example 2

[0043] 5.19g of TEOS, 0.93g of KH550, 1.21g of KH560, and 6.00g of water-in-oil surfactant Span80 were added to 70g of xylene oil, and 10g of deionized water (containing hydrochloric acid solution) with a pH of 2.5 was added dropwise, and then sheared at a high speed of 6000rpm for 10min to form a uniform emulsion, which was then poured into a flask and stirred in an oil bath at 70℃ for 10h to obtain a SiO2 solid product. The solid product was filtered and washed with ethanol as a solvent for multiple times to remove the small organic molecules dissolved in xylene, and then placed in a vacuum freeze dryer, frozen at -60℃ for 3h and vacuum dried for 3h to obtain a SiO2-based Janus material. Since SiO2 is too thin to support regular spheres under large diameter, the prepared product is hollow sphere fragments. SEM results are shown in Figure 6As shown, the sheet thickness reaches 600-800nm. The obtained hollow spheres are dispersed in ethanol and mechanically crushed by an ultrasonic cell crusher for 10 minutes to obtain the required SiO2-based Janus nanosheets, using 3.0s / 3.0s intermittent ultrasound, and the crushing power is 390w. Then the SiO2-based Janus material is crushed and mixed with fluorescein isothiocyanate (FITC, FITC is a fluorescent dye with a specific labeling function for amino functional groups), and then the FITC-stained polymer product is characterized by fluorescence using an Olympus FV1000 laser scanning confocal microscope. FITC is excited under 495nm laser irradiation to produce bright green fluorescence, and its fluorescence image is taken by a laser scanning confocal microscope. The complete spherical and agglomerated fragmented sheet structures appear in the field of view at the same time. After FITC staining and laser excitation, clear green fluorescence is observed only on the fragmented sheet structure, while the complete hollow sphere does not have green fluorescence. This is because after the Janus hollow sphere is broken, the inner surface with amino groups is exposed to the outside on the fragments, and FITC combines with the amino groups on the inner surface. Bright fluorescence can be observed after excitation; since the FITC dye cannot enter the interior of the complete Janus sphere, the amino groups on the inner surface are not labeled by FITC, and the epoxy groups on the outer surface do not react with FITC. No fluorescence is observed after laser excitation, indicating that the amino groups are formed on the inner surface of the SiO2-based Janus material, and the epoxy functional groups are formed on the outer surface of the SiO2-based Janus material.

[0044] Example 3

[0045] 10.41g of TEOS, 0.92g of KH550, 1.20g of KH560, and 6.00g of water-in-oil surfactant Span80 were added to 70g of xylene oil, and 10g of deionized water (containing hydrochloric acid solution) with a pH of 2.5 was added dropwise, and then sheared at a high speed of 6000rpm for 10min to form a uniform emulsion, which was then poured into a flask and stirred in an oil bath at 70℃ for 10h to obtain a SiO2 solid product, which was filtered and washed with ethanol as a solvent for multiple times to remove the small organic molecules dissolved in xylene, and then placed in a vacuum freeze dryer, frozen at -60℃ for 3h and vacuum dried for 3h to obtain SiO2-based Janus hollow spheres. SEM results are shown in Figure 7As shown, the diameter of the hollow sphere is about 60-80 μm, and the shell wall thickness is about 700 nm. The obtained hollow spheres are dispersed in ethanol and mechanically crushed by an ultrasonic cell crusher for 10 minutes to obtain the desired SiO2-based Janus nanosheets, using 3.0s / 3.0s intermittent ultrasound, and the crushing power is 390w. Then the SiO2-based Janus material is crushed and mixed with fluorescein isothiocyanate (FITC, FITC is a fluorescent dye with a specific labeling function for amino functional groups), and then the FITC-stained polymer product is characterized by fluorescence using an Olympus FV1000 laser scanning confocal microscope. FITC is excited under 495nm laser irradiation to produce bright green fluorescence, and its fluorescence image is taken by a laser scanning confocal microscope. The complete spherical and agglomerated fragmented sheet structures appear in the field of view at the same time. After FITC staining and laser excitation, clear green fluorescence is observed only on the fragmented sheet structure, while the complete hollow sphere does not have green fluorescence. This is because after the Janus hollow sphere is broken, the inner surface with amino groups is exposed to the outside on the fragments, and FITC combines with the amino groups on the inner surface. Bright fluorescence can be observed after excitation; since the FITC dye cannot enter the interior of the complete Janus sphere, the amino groups on the inner surface are not labeled by FITC, and the epoxy groups on the outer surface do not react with FITC. No fluorescence is observed after laser excitation, indicating that the amino groups are formed on the inner surface of the SiO2-based Janus material, and the epoxy functional groups are formed on the outer surface of the SiO2-based Janus material.

[0046] Example 4

[0047] 10.40g of TEOS, 0.92g of KH550, 1.21g of KH560, and 5.99g of water-in-oil surfactant Span80 were added to 70g of xylene oil, and 10g of deionized water (containing hydrochloric acid solution) with a pH of 2.5 was added dropwise, and then sheared at a high speed of 8000rpm for 10min to form a uniform emulsion, which was then poured into a flask and stirred in an oil bath at 70℃ for 10h to obtain a SiO2 solid product, which was filtered and washed with ethanol as a solvent for multiple times to remove the small organic molecules dissolved in xylene, and then placed in a vacuum freeze dryer, frozen at -60℃ for 3h and vacuum dried for 3h to obtain SiO2-based Janus hollow spheres. SEM results are shown in Figure 8As shown, the diameter of the hollow sphere is about 15 μm, and the shell wall thickness is about 800 nm. The obtained hollow spheres are dispersed in ethanol and mechanically crushed by an ultrasonic cell crusher for 10 minutes to obtain the desired SiO2-based Janus nanosheets. 3.0s / 3.0s intermittent ultrasound is used, and the crushing power is 390w. Then the SiO2-based Janus material is crushed and mixed with fluorescein isothiocyanate (FITC, FITC is a fluorescent dye with a specific labeling function for amino functional groups). After that, the FITC-stained polymer product is characterized by fluorescence using an Olympus FV1000 laser scanning confocal microscope. FITC is excited under 495nm laser irradiation to produce bright green fluorescence, and its fluorescence image is taken by a laser scanning confocal microscope. The complete spherical and agglomerated fragmented flake structures appear in the field of view at the same time. After FITC staining and laser excitation, clear green fluorescence is observed only on the fragmented flake structure, while the complete hollow sphere does not have green fluorescence. This is because after the Janus hollow sphere is broken, the inner surface with amino groups is exposed to the outside on the fragments, and FITC combines with the amino groups on the inner surface. Bright fluorescence can be observed after excitation; since the FITC dye cannot enter the interior of the complete Janus sphere, the amino groups on the inner surface are not labeled by FITC, and the epoxy groups on the outer surface do not react with FITC. No fluorescence is observed after laser excitation, indicating that the amino groups are formed on the inner surface of the SiO2-based Janus material, and the epoxy functional groups are formed on the outer surface of the SiO2-based Janus material.

[0048] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for characterizing the two-sidedness of SiO2-based Janus materials, characterized in that: The SiO2-based Janus material includes SiO2-based hollow microspheres, the inner surface of the SiO2-based hollow microspheres has amino groups, and the outer surface of the SiO2-based microspheres has epoxy functional groups. The SiO2-based Janus material is crushed and mixed with isothiocyanate fluorescein, and the SiO2-based Janus material is subjected to infrared testing.

2. The method according to claim 1, characterized in that The preparation method of the SiO2-based Janus material comprises: Mixing a silicon source with silane coupling agents KH550, KH560, a water-in-oil surfactant and an organic solvent to obtain a mixed oil phase; Mixing the mixed oil phase with an aqueous solution containing a pH adjuster while stirring to obtain a mixed emulsion; heating the mixed emulsion for reaction; The product obtained by the heating reaction is freeze-dried to obtain the SiO2-based Janus material.

3. The method according to claim 2, characterized in that The silicon source includes at least one of TEOS, tetramethyl silicate and propyl orthosilicate.

4. The method according to claim 2 or 3, characterized in that The water-in-oil surfactant includes at least one of Span80, Span85 and Span60.

5. The method according to claim 2, characterized in that The organic solvent includes at least one of xylene oil, toluene and liquid paraffin.

6. The method according to claim 2, characterized in that The mass ratio of the silicon source to the silane coupling agent KH550, the KH560, the water-in-oil surfactant and the organic solvent is 100:(15-20):(20-40):(100-130):(1000-1500).

7. The method according to claim 2, characterized in that The pH of the aqueous solution containing the pH adjuster is 2-5.

8. The method according to claim 2, characterized in that The mass ratio of the mixed oil phase to the aqueous solution containing the pH regulator is (100-150):(15-20).

9. The method according to claim 2, characterized in that The heating temperature is 70-80° C. and the heating time is 10-12 hours.

10. The method according to claim 1 or 2, characterized in that The SiO2-based Janus material has a particle size of 10 μm-80 μm and a wall thickness of 0.5 μm-1.5 μm.